A Hybrid Approach for Congestion Control in Vehicular Ad-Hoc Networks - موسى حسن (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, mobile vehicle networks and congestion in this type of networks were identified, and a group of congestion control algorithms was reviewed. A hybrid algorithm that works to adapt the data transmission rate and the transmission power capacity for vehicles in Ad-Hoc networks is proposed. The proposed hybrid algorithm is based on data rate control together with transmission power adaptation to improve the network performance. Simulation results show that the proposed hybrid algorithm achieves better performance, compared to the reference studies, in terms of four parameters. Higher network throughput, higher PDR (Packet Delivery Ratio), lower PLR (Packet Loss Ratio), and lower CBR (Channel Busy Ratio) were obtained, compared to the reference algorithms that deal separately with data transmission rate or power transmission capacity.